Cyto and genotoxicity of positive and negative coated Silica nano particles on Celomocytes of earthworms Eisenia fetida (Oligocheta, Annelida) - Di Marzio, Walter Dario (2018)
To understand and assess the effects of nanoparticles (NPs) on the environment, should be well established quantitatively the concentration-response relationships. Also relate the potential effects on selected variables of response with the exposure to sub-lethal levels of NPs. In this work, we describe the ecotoxicological evaluation of negative and positive coated silica NPs (Si-Nps) on coelomic cells from Eisenia fetida. The cytotoxicity of earthworm coelomocytes, expressed as LC50-1hour, was equal to 73.94 and 116.93 μg/mL for positive and negative Si-NPs, respectively. Genotoxicity were determined on the basis that the Si-NPs promote the generation of reactive oxygen species (ROS) once added on cell membranes, or entered in cells. In this case both types of NPs were genotoxics even at the lowest tested concentration equal to 1 μg/mL.